Mathematical Model of Landslides with Curved Sliding Plane Using Fracture Criterion of Solid Soil-Rock System - Ikah Ning Prasetiowati Permanasari; Lilik Hendrajaya; Gunawan Handayani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Alluvial cliff with high slope and step has been known to cause curving sliding plane. This phenomenon is adopted as a knowledge, but it has never been studied theoretically. In this paper, mathematics derivation phenomenon is proposed using special model of 11 fracture criterion ????-????. The quantity of ???? is A???? 2 with A is a friction coefficient of stress ???? 2 . The failure model was substituted to the corresponding Mohr circle resulting the expected curve. The curve was used to measure the observed field profile to obtain the friction coefficient A.